Eye-hand decoupling deficits in young adults with concussion history from adolescence: Issues with task novelty or task demand?. (11th June 2022) - Veillon-Bradshaw, Michelle; Phillips, Brandon; Jones, Briasha D.; Dalecki, Marc
Highlights: Young adults with concussion history from adolescence showed difficulties with adapting to perform complex motor skills that require eye-hand decoupling. Their initial movement direction may be off when performing new and complex every-day or sport-related tasks that require eye-hand decoupling. Practitioners and coaches should allow adequate time for this demographic to adjust and adapt their movements during beginning learning periods of such tasks. Abstract: The present study expands previous work that reported eye-hand decoupling (EHD) deficits in young adults with concussion history from adolescence. Here, we examine whether these deficits in movement planning (i.e., larger initial direction error) can be linked to difficulties with adapting to new task constraints or meeting ongoing task demands. Data from 21 young adults with concussion history from adolescence (CH) and 20 no history controls (NoH) were analyzed. All participants (Mean = 21 yrs.) performed two eye-hand coordination tasks, a standard task with vision and motor action in alignment, and an EHD task with eye- and hand movement direction spatially decoupled, with twenty trials per task condition. The re-analysis focused on the EHD condition as deficits were found for this task only in prior work. Trials were split into 5 blocks (trial 1–4, 5–8, 9–12, 13–16, 17–20), which included one movement to each of four target directions, and were analyzed across blocks and groups. The CH group had a larger initial direction error during blocks 1–2 but not in blocks 3–5. Our findings suggest that young adults with concussion history from adolescence can have difficulty with adapting to new task constraints associated with complex skill performance during a short series of trials.